‘Usman ‘Ibn ‘Affan dan ‘Ali Ibn Abi Talib (Nepotisme dan Majlis Tahkim) - Beti Mulu (Institut Agama Islam Negeri (IAIN) Kendari, 2008)
Khalifah Usman ibn 'Affan was the third khalifah after Abu Bakardan Umar ibn Khattab. He was born in the sixth year of the elephant year in 576 AD He embraced Islam and performed the Prayer on the auction of Abu Bakr. Khalifah Usman is a wealthy merchant, very generous to the interests of Islam and Muslims.Caliph Usman Bin Affan was elected as the third Caliph in a deliberative committee headed by Abdurrahman Bin Auf who had been appointed by Caliph Umar Bin Khattab. He served as a caliph for 12 years. The first six years recorded the progress made for the progress of Islam. And in the last six years there arose rebellion from the Islamic community due to allegations addressed to the Caliph Usman Bin Affah that he run the wheels of government nepotism. The greatest effort of Caliph Uthman for the benefit of Muslims is the compilation of the Qur'an by performing the uniform readings known today by the name of al-Mushaf.In the reign of Caliph Usman Bin Affan has been exploited by his family of the Umayyads to gain power and wealth that led to allegations of nepotism practice in running the government. That gave rise to rebellion against the Caliph of Uthman and to the murder of the Caliph Usman ibn 'Affan.Ali Ibn Abi Talib is the cousin of the Prophet Muhammad SAW. He was born at the time of the prophet Muhammad was twenty-nine years old.Ali is the first generation who converted to Islam. He always accompanied the Prophet Muhammad in the struggle to uphold Islam both in Mecca and in Medina. Khalifah Ali ibn Abi Talib was named the Caliph by the majority of Muslims in the mosque of Madinah in 656 AD. His political policy dismissed the governors appointed by Uthman's Caliph and withdrew the land he had granted to the population, causing the Umayyad families to strengthen the ranks of supporting Muawiyah against the Caliph Ali ibn Abi Talib. Similarly Aisha, Talhah and Zubeir in Basrah on the grounds of the death of the Caliph Usmanibvn 'Affan. Finally, there was a Jalal war followed by the Siffin war which ended with the tahkim that dismissed Ali from the typical Islamic post and raised Muawiah on the tactics and engineering of Amr ibn al-Ash. Hence, some of Ali's followers declared their exit from Ali's group called the Khawarij. In the khawarijlah khalifah Ali's assassination in 40 H.